KSZTAŁCENIE INTERKULTUROWE W DYDAKTYCE JĘZYKA NIEMIECKIEGO W POLSCE I W BADANIACH GERMANISTÓW. ANALIZA PORÓWNAWCZA WYBRANYCH DOKUMENTÓW I MATERIAŁÓW GLOTTODYDAKTYCZNYCH - Adamczak-Krysztofowicz, Sylwia; Mihułka, Krystyna (Neofilolog, 2019)
This article is intended to contribute to the academic debate on inter-cultural German language teaching and the relevant research in Poland. The authors present a critical overview and analysis of selected constitu-ent aspects of intercultural education and keywords which are im-portant for the evaluation of goals and content within the framework of interculturally-oriented teaching of German in Poland. The authors also discuss the form of presentation of intercultural aspects of educa-tion in The Common European Framework of Reference for Languages: Learning, teaching, assessment (Council of Europe, 2001), in the Polish core curriculum and in selected German language teaching materials which are meant to shape the intercultural competence of Polish learn-ers at different levels of proficiency and in different types of schools.